Representation of the cartoon controversy on the U.S. newspapers - Yüksel, Yusuf; Akbulut, Ayhan (Journal of Human Sciences, 2015)
Cartoon Crisis composed one of the most comprehensive international security problems of the last decade. A Danish newspaper, Jyllands-Posten, published 12 cartoons to satirize Prophet Mohammed in September 2005 which resulted in boycotts, anger and violent protest and thus a global conflict. The dispute over the cartoons has brought out the questions about the relations between the Islamic World and the West, the role of media on those relations, the limits of freedom of speech and right to protests and violence. This study aimed to find out how the cartoon controversy was represented in the US news media and the difference between newspapers depending on the rate of Muslim population in their circulation area. A content analysis of Detroit Free Press, Herald News, Omaha World-News and Wyoming Tribune-Eagle newspapers are used to test the hypothesis about the publication of the cartoons and reaction of the Muslims to this issue. The findings suggest that the newspapers published in Muslim diverse communities are likely to draw more attention to the controversy. However, the difference is not significant. All of the four newspapers present negative views not only about the publication of the cartoons but also the reaction of the Muslims.